Pengembangan Perangkat Pembelajaran Matematika Berbasis Pendekatan Penemuan Terbimbing Berbantuan Geogebra - Khumaeroh Dwi Nur'aini; Juliana R Untayana; Nuraeni N. C Putri (Musamus Journal of Mathematics Education, 2022)
Abstrak: Tujuan penelitian ini adalah untuk mengembangkan produk perangkat pembelajaran matematika SMP menggunakan pendekatan penemuan terbimbing berbantuan GeoGebra untuk meningkatkan kemampuan komunikasi matematis siswa SMP, Produk yang dikembangkan terdiri dari RPP, LKS dan TKKM, dengan menggunakan desain 4-D yaitu define, design, develop, and disseminate. Penelitian dilaksanakan di SMP Negeri II Merauke sebagai uji coba lapangan dengan jumlah siswa 32 orang. Analisis data dilakukan secara kualitatif dan kuantitatif. Setelah melalui tahapan validasi produk, RPP memperoleh nilai 167,5, LKS memperoleh nilai 86,5, dan TKKM memperoleh nilai 89,5 sehingga produk termasuk kategori valid. Hasil uji kepraktisan oleh guru memperoleh nilai 87,5 dan uji kepraktisan oleh siswa memperoleh nilai 49,40 sehingga produk perangkat pembelajaran memenuhi kategori sangat praktis. Untuk Uji keefektifan, hasil tes kemampuan komunikasi matematis menunjukkan bahwa lebih dari 75% siswa telah mencapai KKM ≥ 75, sehingga produk perangkat pembelajaran memenuhi kategori efektif. Abstract: This is a development research project with four stages: define, design, develop, and disseminate. This study was conducted as a field trial with 32 students at SMP Negeri II Merauke. Data analysis was performed by grouping the data based on product qualifications, and then calculations were performed to obtain the average value included in the Likert scale rating category. The product of this research is a set of junior high school mathematics learning tools that use a guided discovery approach and are aided by GeoGebra to improve the mathematical communication skills of junior high school students. These tools include lesson plans, worksheets, and TKKM. Following the product validation stages, the RPP received a value of 167.5, LKS received an 86.5, and TKKM received an 89.5, indicating that the product is in a valid category. The practicality test results obtained 87.5 teachers' practicality and practicality students scored 49.40, indicating that the learning device products are very practical, and the mathematical communication skills test results show that more than 75 percent of students achieved KKM ≥ 75, indicating that the learning device products are effective. Because the resulting product sets meet valid, practical, and effective criteria, they are appropriate for use in classroom learning.